SEMANTIC COMPREHENSION OF LEXICAL CONTENT OF THE ENGLISH BOOK JACKETS - Anna Smoliana (European Scientific Journal, ESJ, 2013)
The article deals with the peculiarities of organizing the information on the English book dust jackets, lexico-semantic properties of the language units and relations between the lexical items. The main semantic dimensions and semantic fields were identified considering the vocabulary of English book jackets. Application of the semantic analysis gave us proofs that language on the English book dust jackets is organized in a mental lexicon with particular semantic features that were demonstrated via semantic dimensions and semantic fields.English book dust jacket is presented as an informational-advertising type comprising texts with their specific features. The mini-texts are organized in the informational blocks that reveal diverse functions. That’s why it seems to be crucial to consider language units from different perspectives – lexical, semantic and cognitive and take a view at different kinds and types of meanings to show how they fit into the total composite effect of a book jacket lexicon.The paper presents a first look at the semantic structure of the information associated with the vocabulary of the English book jackets and aims at analyzing the lexemes and attempt to organize them in the semantic fields. We conducted a semantic analysis and defined semantic fields created for getting general overview of a particular domain of content.